Kandungan Kimia dan Aktivitas Sitotoksik Ekstrak dan Fraksi Herba Anting-anting terhadap Sel Kanker Payudara MCF-7 - Febriyanti, Maya; Supriyatna, .; Abdulah, Rizky (Indonesian Research Gateway)
Acalupha indica, belongs to Euphorbiaceae family, is annual herb which distributed widely in Asia, including Indonesia. Extract and fraction of Acalypha indica were sreened for phytochemical constituents and investigated for its cytotoxicity against human breast cancer MCF-7 using MTT assay. Ethanolic extract of A.indica showed cytotoxicity against MCF-7 with an IC50 225 μg/ml. While for the fraction, ethyl acetate fraction showed best cytotoxicity compared to n-hexane and water fraction with an IC50 387 μg/ml. Phytochemical screening to the ethyl acetate fraction showed that the fraction contain flavonoids, polyphenols, monoterpenes and sesquiterpenes, triterpenoids, and quinones.Keywords : Acalypha indica, cytotoxicity, MCF-7, MTT assay